Computational fluid-structure interaction methods and applications - Bazilevs, Yuri (Wiley, 2013)
"Computational Fluid-Structure Interaction is a complete, self-contained reference that takes the reader from the fundamentals of computational fluid and solid mechanics all the way to the state-of-the-art in CFSI research"-- Provided by publisher.